Juridical Analysis Of The Regulation On Prevention And Handling Of Sexual Harassment In Indonesian Higher Education Institutions - Prihatna, Budi Ageng; Delano, Teddy; Gulo, Nimerodi (JURNAL HUKUM SEHASEN, 2025)
The objective of this research is to analyze the legal framework regarding the prevention and handling of sexual harassment in higher education institutions. The research method used in this study is normative juridical. The findings of this study reveal that Law Number 12 of 2022 stipulates criminal liability for perpetrators of sexual violence offenses, including imprisonment and fines. Regarding criminal liability under Law Number 12 of 2022, there is potential for sentencing disparities among judges, as the law only regulates maximum penalties. In addition to imprisonment, fines, or other penalties, judges are also required to determine the amount of restitution for sexual violence offenses punishable by imprisonment of four (4) years or more. Meanwhile, Ministerial Regulation of Education, Culture, Research, and Technology (Permendikbudristek) Number 30 of 2021 provides guidelines for higher education institutions in preventing and handling sexual violence within universities. The targets of sexual violence prevention and handling include: a. Students; b. Educators; c. Educational staff; d. Campus residents; and e. The general public who interact with students, educators, and educational staff in the implementation of the Tridharma. The provisions on administrative sanctions that can be imposed on perpetrators of sexual violence in higher education institutions include minor administrative sanctions, moderate administrative sanctions, and severe administrative sanctions. There is a need for clear indicators regarding the classification of administrative sanctions to determine how a sanction is categorized as minor, moderate, or severe.